Щодо використання наближеного розрахунку температурного поля стрижня, що закріплений з одного кінця - Пустовалов, Володимир Миколайович; Чижев, Д. А. (НТУ "ХПІ", 2009)
The approximate prediction of a temperature field of a bar is widely used in various areas of heat engineering. In the paper, the error estimation caused by using of simplifying assumption is putting forward.
Keywords: теплотехнічні пристрої; робочі лопатки; тепловий потік